KALIMAT TANYA DALAM BAHASA INGGRIS DAN BAHASA TANIMBAR SUATU ANALISIS KONTRASTIF - Oratmangun, Yeni Derika (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This study is an attempt to describe and analyze the English and Tanimbar language which focuces on the interrogative sentences in relation to their form and function in both languange based on Aarts and Aarts theory’s and to compare using by Lado’s theory.The English and Tanimbar Language are two languages from different language families. English it is included in Indo-European and Tanimbar Language it is included in Austronesian one. Each of them has its own characteristics.The English data have been collected from books, whereas the data of Tanimbar language have been collected by interviewing some informants using contrastive analysis approach the data are then analyzed and described.The result shows that forms of interrogative sentences in English are yes-no question, tag question and interrogative-word question while in Tanimbar language has two forms such as in yes-no question and interrogative word question. English and Tanimbar language have similarities, in the form of yes-no question and interrogative word question. The difference in English question word is at the beginning of sentence and Tanimbar language at the beginning and the end of sentence. Keywords : Interrogative Sentences, English and Tanimbar Language, Contrastive Analysis. Analysis.